Characterization of barley ert-c mutants - Floberg Karlsson,Bill (2025)
The barley erectoides (ert) mutants are characterized by an erect growth habit, a short and compact spike and often a short culm length. The ert-c mutant group consists of 40 allelic mutants and is thus one of the largest groups. The aim of this study was to identify the ert-c gene. The genomes of eight ert-c mutants have been sequenced and a set of candidate genes were identified. In the present study, I have analyzed if any of the suggested candidate genes is the causal gene of the ert-c mutants. The most promising candidate gene was encoding a myb transcription factor (HORVU.MOREX.r3.3HG0256690), which showed mutations in seven of the 40 mutants. Crosses between a set of ert-c mutants excluded a few accessions as ert-c mutants. Still, the crosses also showed that most of the ert-c mutants indeed are allelic. I suggest that further analysis have to be performed to rule out if the identified myb gene is the sought after ert-c gene. I postulate that many of the non-identified mutations then have to be located in regulatory regions which are unknown today.